The Analysis of Post-Flood Flood Surveillance Activities in Torue District: Parigi Motong Regency in 2022 - Laba, Stefiani Bengan (Tadulako University, 2023)
Post-disaster surveillance played a crucial role in disaster management, including the flash flood disaster. In addition to focusing on disaster victims, health workers and health posts are also required to carry out surveillance activities in order to get a follow-up plan as soon as possible in a post-disaster situation. This study aims to evaluate post-disaster surveillance implementation based on 6 post-disaster indicators. This type of research is a quantitative descriptive method using field research methods through observation and interviews. The research targets were disease reports at the time of the disaster and a number of informants, namely one Secretary of the Parigi Health Service, including health workers at each Health Post. The results of this study indicate that the Torue Disaster Task Force has carried out environmental sanitation monitoring activities, surveillance of infectious diseases and malnutrition that may arise, outbreaks of communicable diseases and malnutrition, and community empowerment. Of the 6 indicators of post-disaster surveillance, 5 indicators have been conducted and 1 indicator namely mental health problem recovery has not been implemented. The indicators that have been conducted have almost reached the applicable standards.